Morte e poesia na Roma antiga: luto, lamento e consolação nas Silvae de Estácio (século I EC) - Modesto, Murilo Tavares (2022)
This research is a study about the representations of lament in six consolatory poems written by Publius Papinius Statius (c. 45 – 96 CE), the Siluae 2.1, 2.6, 3.3, 5.1, 5.3 e 5.1. Each of these poems was initially intended for a specific man, a man in grief for someone’s death, and, later, published throughout the Siluae’s collection of five books. Our goals in this dissertation are to analyze how the representations of male lament in Statius’ consolations attended to possible interests of their aristocratic recipients regarding issues about death and to indicate to what extent the poetic descriptions of intense lamentation were in accordance with the expectations of Siluae’s reader circles. We start from the hypothesis that Statius’ representations of aristocratic men’s lament followed the traditional pattern of Latin poetic rhetoric to deal with mourning and, therefore, responded to what his readers expected. With the theoretical and methodological proposals of the Cultural History of the book and of reading, we investigated the conditions of production and circulation of these texts, delimiting the context of the research in the readers’ groups of the high social strata of Rome, Naples and their surroundings during the end of the first century of Common Era. We approach Statius’ social background, Siluae’s poetic characteristics and the poet’s relations with his bereaved recipients and with his reader circles. We also present an overview of the Roman practices surrounding death, highlighting the funeral ceremonies’ events and the importance given to the deceased’s memory, and we discuss the ancients’ expectations on mourning and on consolatory literature, evaluating the approaches to lamentation by Latin philosophers, rhetoricians and poets. Having explained these questions, we analyze Statius’ consolatory rhetoric about the lament of those bereaved addressees. We also examine these poems’ connection with the context of slavery and patronage, since among the deceased honored there were two freed boys and one enslaved child, while one of the recipients and another deceased were imperial freedmen. In this sense, we comment on the mortuary expectations for Roman slaves and freedmen, especially in the context of the rise of imperial freedmen. Our reflections, therefore, analyze the representations of lament in the Siluae’s consolations on the likely expectations of those addressed and their readers.